Paramount: language in use (beginner self study workbook with answer key) - Doff, Adrian (Paramount books Karachi, 2000)
"PARAMOUNT: Language in Use (Beginner Self-Study Workbook with Answer Key)" is a practical resource designed for learners new to a language. The workbook focuses on essential language skills through a variety of exercises, including vocabulary, grammar, and sentence construction. Each section is user-friendly, allowing learners to practice independently, while the included answer key helps reinforce understanding and self-assessment. This workbook is ideal for beginners looking to build a solid foundation in their language learning journey.